2017
DOI: 10.1007/s00213-017-4584-y
|View full text |Cite
|
Sign up to set email alerts
|

Social defeat disrupts reward learning and potentiates striatal nociceptin/orphanin FQ mRNA in rats

Abstract: Rationale Mood disorders can be triggered by stress and are characterized by deficits in reward processing, including disrupted reward learning (the ability to modulate behavior according to past rewards). Reward learning is regulated by the anterior cingulate cortex (ACC) and striatal circuits, both of which are implicated in the pathophysiology of mood disorders. Objectives Here we assessed in rats the effects of a potent stressor (social defeat) on reward learning and gene expression in the ACC, ventral t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 76 publications
(129 reference statements)
3
36
0
Order By: Relevance
“…Another recent study demonstrated negative correlations between reward learning and N/OFQ peptide mRNA levels in the cingulate gyrus and with NOPr mRNA levels in the ventral tegmental area 61 . Overall, the results align with the reward system disruptions noted in schizophrenia, in which the existence of deficits is well supported by the literature 3 .…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Another recent study demonstrated negative correlations between reward learning and N/OFQ peptide mRNA levels in the cingulate gyrus and with NOPr mRNA levels in the ventral tegmental area 61 . Overall, the results align with the reward system disruptions noted in schizophrenia, in which the existence of deficits is well supported by the literature 3 .…”
Section: Resultsmentioning
confidence: 93%
“…These differential findings may arise due to species differences, but may also indicate a dynamic role of NOPr modulation of stress reactivity. Social stress (in different forms) increased N/OFQ and NOPr mRNA in the hippocampus, central amygdala, paraventricular nucleus, and in the nucleus accumbens shell 58 61 .…”
Section: Resultsmentioning
confidence: 99%
“…However, the SPT is not a test for the dimensions that underlie deficient reward interest in depression, but rather a test for sustained responsiveness during consummatory behavior (Cuthbert and Insel, 2013 ). Tests of reward bias with analogy to the human test described above (Pizzagalli et al, 2005 ) have been developed for rats (Der-Avakian et al, 2013 , 2016 , 2017 ). In one test version, rats are trained to discriminate between two tone stimuli by pressing the specific lever associated with each tone.…”
Section: Introductionmentioning
confidence: 99%
“…In the HT, it is expressed in nuclei promoting aggression (MPOA, VMH and SUM). Social defeat increases STR NOP [Der-Avakian et al, 2017]. Structurally, it is related to DYN, the other OP associated with negative innates.…”
Section: Aggression: Nociceptin (Noc N/ofq)mentioning
confidence: 92%